Divergent synthetic route to new cyclopenta[c]pyran iridoids: syntheses of jatamanin A, F, G and J, gastrolactone and nepetalactone. Issue 4 (8th December 2015) - Sim, Jaehoon; Yoon, Inah; Yun, Hwayoung; An, Hongchan; Suh, Young-Ger
Abstract : Six natural iridoids including jatamanin A, F, G and J, gastrolactone and nepetalactone have been synthesized via the efficient transformation of a core cyclopenta[ c ]pyran intermediate. Abstract : Six natural iridoids including jatamanin A, F, G and J, gastrolactone and nepetalactone have been synthesized via the efficient transformation of a core cyclopenta[ c ]pyran intermediate. Key features of the syntheses include the stereoselective construction of the core cyclopenta[ c ]pyran skeleton of the iridoid lactones via a Pd(0)-catalyzed intramolecular allylic alkylation, and the facile transformation of the common intermediate into natural iridoids.